Entrepreneurial Behavioral of Garlic Farmers in the Garlic Production Center Area, Sembalun District, East Lombok Regency - Sri Maryati; Idiatul Fitri Danasari; Ni Made Wirastika Sari; Ni Luh Sri Supartiningsih; Taslim Sjah (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to identify and analysis of the entrepreneurial behaviour of garlic farmers as entrepreneurial farmers in the garlic production center area in Sembalun District, East Lombok Regency. This research was conducted in March–May 2023. The data used were primary data obtained through interviews with 80 farmers in Sembalun Bumbung and Sembalun Lawang Village; both locations were chosen because they were villages with the highest number of farmers, production, and garlic land area in Sembalun District. The analysis of the Entrepreneurial Behavioural Index (EBI) is carried out statistic descriptive using FAO ideas. It is classified into four components: Entrepreneurial Qualities, Entrepreneurial Competencies, Managerial Competencies, and Technical Competencies. The results showed that the entrepreneurial activities of garlic farmers in the national garlic production center area of Sembalun District, East Lombok Regency, were still dominated by low levels of entrepreneurial activity in the criteria of entrepreneurial qualities  (63.75%) and entrepreneurial competencies (51.25%). While the Managerial  Competencies criteria are at a high level (51.25%), and the Technical Competencies criteria are at a moderate level (51.25%). As consequences, training, farmers’ field schools, and extension services are still needed to improve the quality and competence of garlic farmers as a whole.